2014
DOI: 10.1016/j.dci.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on antigen presenting cells in zebrafish

Abstract: Antigen presentation is a critical step in the activation of naïve T lymphocytes. In mammals, dendritic cells (DCs), macrophages, and B lymphocytes can all function as antigen presenting cells (APCs). Although APCs have been identified in zebrafish, it is unclear if they fulfill similar roles in the initiation of adaptive immunity. Here we review the characterization of zebrafish macrophages, DCs, and B cells and evidence of their function as true APCs. Finally, we discuss the conservation of APC activity in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 105 publications
1
29
0
Order By: Relevance
“…Teleost B-cells exhibit additional phagocytic and microbicidal functions not typically seen in higher vertebrates (Li et al, 2006;Øverland, Pettersen, Rønneseth, & Wergeland, 2010), and they can also function as initiating antigen-presenting cells, linking the innate and adaptive immune systems in zebrafish (Lewis, Del Cid, & Traver, 2014;Zhu et al, 2014). In teleosts, intestinal mucosal immunity is largely dependent on B-cells acting as the primary responders to perturbation, but our understanding of their origins and full spectrum of functions in maintaining gut homeostasis is still limited (see Parra, Korytář, Takizawa, & Sunyer, 2016 Immersion infection can be used for larvae beginning when the mouth first opens at around 3 dpf (Ng et al, 2005).…”
Section: Adaptive Immunity and The Gi Tractmentioning
confidence: 99%
“…Teleost B-cells exhibit additional phagocytic and microbicidal functions not typically seen in higher vertebrates (Li et al, 2006;Øverland, Pettersen, Rønneseth, & Wergeland, 2010), and they can also function as initiating antigen-presenting cells, linking the innate and adaptive immune systems in zebrafish (Lewis, Del Cid, & Traver, 2014;Zhu et al, 2014). In teleosts, intestinal mucosal immunity is largely dependent on B-cells acting as the primary responders to perturbation, but our understanding of their origins and full spectrum of functions in maintaining gut homeostasis is still limited (see Parra, Korytář, Takizawa, & Sunyer, 2016 Immersion infection can be used for larvae beginning when the mouth first opens at around 3 dpf (Ng et al, 2005).…”
Section: Adaptive Immunity and The Gi Tractmentioning
confidence: 99%
“…The zebrafish model is a powerful system in which to directly observe immune cell function (Hall et al, 2013(Hall et al, , 2014Harvie and Huttenlocher, 2015;Keightley et al, 2014;Lewis et al, 2014;Torraca et al, 2014). Various transgenic reporter lines marking specific innate immune cell lineages have provided a window to explore their function within an intact host.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, expression of MHC I molecules could be related to Cytotoxic T cell (CD8+) and long‐term immunity after infection and vaccination (Bulter, Nolz, & Harty, ; Lo, Dunn, Ong, Metcalf, & Soloski, ). The B‐lymphocytes and macrophages are antigen‐presenting cells on MHC I molecule for the activated CD8 + that initiate a lytic attack of target cells containing pathogens (Lewis, Del Cid, & Traver, ; Wherry & Masopust, ). Furthermore, a previous study had shown that the outer membrane proteins (OMPs) of V. harveyi can evoke the production and activation of CD8 + with antigen‐presenting cells through MHC I in large yellow croakers, Pseudosciaena crocea (Zhang, Yu, & Qian, ).…”
Section: Discussionmentioning
confidence: 99%